PERAN KEMITRAAN BADAN USAHA MILIK NEGARA TERHADAP USAHA KECIL MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2008 TENTANG USAHA MIKRO, KECIL DAN MENENGAH (STUDI KEMITRAAN PT. TELKOM CDSA MEDAN DENGAN “ITA MODE”) - Dila Afifah; Budiman Ginting; Ramli Siregar (Universitas Sumatera Utara, 2013)
The thesis is motivated by the interest in the issue of the State-Owned Enterprise (BUMN) partnertship toward small enterprises. In this thesis, the problem is how the role of State-Owned Enterprise partnership in empowering small enterprises according to Basic Law Constitution No.20 of 2008 about Small-Medium Enterprises, the fundings which become the barriers in doing the partnership between State-Owned Enterprise an the small enterprise as the constructed partner. Small business that became one of the largest sources of revenue must be considered specifically in terms of its development. Therefore the State-Owned Enterprise runs the partnership program toward small enterprise in order to empower small enterprises in national economic sector. Research methods that are used within tha data obtained in support of this is Descriptive Normative Legal Reseach Methods in the early stages where the authors conducted a study to the secondary data which is legislation rule related to and sebsquent authors conducted research through interview techniques and collecting materials from the speakers at Telkom CDSA Medan and Ita Mode to know hoe the implementation of the State-Owned Partnership toward small enterprises. The role of State-Owned Enterprises to small business partnership is to provide assistance steamy soft loans, where the loan banyuan used for the development of the business. State-Owned Enterprise does not only provide assistance in the form of soft loans, but also provide training and trade promotion small business partners who become surrogates. State-Owned Enterrprise partnership contributes a very big role for small business. It can be seen from the development of small business that the increasing both in terms of revenue and business management. If it is related with Basic Law Constitution No.20 of 2008 about Small-Medium Enterprises, within a partnership between the state with small businesses, the state has implemented the partnership with both the small business. Kata Kunci : Kemitraan, BUMN, Usaha Kecil